General intellectual functioning as a buffer against theory-of-mind deficits in individuals at ultra-high risk for psychosis - Hur, Ji-Won; Byun, Min Soo; Shin, Na Young; Shin, Ye Seul; Kim, Sung Nyun; Jang, Joon Hwan; Kwon, Jun Soo (Schizophrenia research, 2013)
The influence of neurocognition, including general intelligence, on theory of mind (ToM) among patients with schizophrenia spectrum disorder is controversial. The purpose of the present study was to identify the influences of the non-ToM cognition and general intelligence on ToM performance in individuals at ultra-high risk (UHR) for psychosis. Fifty-five UHR subjects and 58 healthy controls (HCs) completed neurocognitive, verbal, and nonverbal ToM tasks. UHR individuals showed poorer performance in the two verbal ToM tasks, the false-belief task and the strange-story tasks. Moreover, the UHR subjects displayed poorer recall on the interference list of the verbal learning test. Linear regression analysis revealed that neurocognitive functioning, including executive functioning, working memory, and general intelligence, accounted for significant amounts of the variance in the results for UHR individuals: 20.4% in the false-belief task, 44.0% in the strange-story task, and 49.0% in the nonverbal cartoon task. Neurocognition, including general intelligence, was not a significant contributor to performance on ToM tasks in HCs. ToM deficits were not noted in UHR individuals with above-average IQ scores (≥110) compared with UHR subjects with IQ scores less than 110, who displayed significant differences on all ToM tasks compared with HCs. The present results suggest that ToM deficits in UHR individuals are complex and may be influenced by non-ToM cognition. Our findings are discussed in relation to the role of neurocognitive abilities in ToM-related impairments in UHR individuals.